Parameters controlling weld bead profile in conduction laser welding - Ayoola, Wasiu; Suder, Wojciech; Williams, Stewart (Cranfield University, 2017)
This file contains all data set presented in the above paper.
Keywords: 'CON vs CS'; 'Manufacturing Processes and Technologies (excl. Textiles)'